Optimizing Factors in Increasing the Value of Indonesian Islamic Banking - Dwianto, Agus; Triyono, Triyono; Witono, Banu (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to explore the optimization of factors influencing the value of Islamic banking in Indonesia. Key factors examined include Islamic Intellectual Capital (IIC), Islamic Corporate Governance (ICG), Sharia Maqashid Index (SMI), Islamic Financial Performance (IFP), and their mediation relationships with Islamic Firm Value (IFV). Using a sample encompassing multiple quarters from three Islamic banks in Indonesia and employing the SmartPLS.4 methodology, the findings indicate significant relationships between IIC and ICG with IFP, which in turn impacts IFV. However, SMI was found to have no statistically significant effect. This study offers insights into enhancing the value of Islamic banking in Indonesia. Although it comes with certain limitations, such as the use of quarterly samples, it paves the way for future research exploring additional factors and the social, academic, and Islamic implications of Islamic banking, providing a more holistic understanding of its role in the Indonesian financial landscape.